Counseling Empathy in the Digital Era: Building Emotional Connections with Elementary School Students - Sholikhin, Sholikhin; Muniroh, Siti Mumun (MO.RI Publishing, 2023)
This research was conducted to explore the impact of empathetic counseling using video call technology and specialized applications on elementary school students in addressing their emotional issues and enhancing their academic performance. The rapidly evolving digital era has brought complex challenges regarding the emotional well-being of children in elementary schools, making the role of counselors increasingly vital. The objective of this study is to investigate the effectiveness of empathetic counseling approaches through digital platforms in assisting students to overcome emotional problems and enhance their self-confidence. The research methodology involves an in-depth analysis of scientific publications related to empathetic counseling in the digital era, focusing on the empathetic counseling strategies implemented by counselors in the digital elementary school environment. The findings indicate that empathetic counseling approaches through video call technology and specialized applications have a positive impact, helping students feel heard, understood, and supported. However, the study also identifies limitations in involving parents' cooperation and technical aspects of using digital platforms.